2019
DOI: 10.1016/j.abb.2019.108122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human lactoferrin on calcium signaling and functional responses of human neutrophils

Abstract: Lactoferrin is a non-heme iron-binding glycoprotein with multiple health-beneficial functions including antimicrobial, antioxidant, anticarcinogenic, and immunomodulatory effects. There is emerging evidence that neutrophils may serve as targets of lactoferrin in vivo, and here we show how recombinant human lactoferrin (rhLf) can contribute to this regulation. Indeed, our results demonstrate that rhLf binds efficiently to human neutrophils and induces a variety of early cellular responses such as mobilization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
1
5
1
Order By: Relevance
“…Pastori et al had reported LF to reduce oxidative stress induced by tears of patients with keratoconus [ 20 ]. Previous studies have reported significant inter-group differences in peripheral blood lymphocyte subset ratios, neutrophils phagocytic function, and NK cell cytotoxicity [ 19 , 21 , 22 , 23 , 24 , 25 ], while the present study did not report any change in the number of eosinophils. The findings of previous studies implied that eLF administration might affect the human immune system [ 26 ], thereby reducing conjunctival injection in patients with AKC.…”
Section: Discussioncontrasting
confidence: 91%
“…Pastori et al had reported LF to reduce oxidative stress induced by tears of patients with keratoconus [ 20 ]. Previous studies have reported significant inter-group differences in peripheral blood lymphocyte subset ratios, neutrophils phagocytic function, and NK cell cytotoxicity [ 19 , 21 , 22 , 23 , 24 , 25 ], while the present study did not report any change in the number of eosinophils. The findings of previous studies implied that eLF administration might affect the human immune system [ 26 ], thereby reducing conjunctival injection in patients with AKC.…”
Section: Discussioncontrasting
confidence: 91%
“…However, a more important function of the LTF is the host immune response for infection or inflammation (Lambert, 2012). The wide spectrum of biological activity of LTF also includes antimicrobial (Yoshida et al, 2000), antiviral (Waarts et al, 2005), antifungal (Andersson et al, 2000), immunoregulatory, and antiinflammatory properties (Grigorieva et al, 2019). Additionally, LTF plays a role in cell proliferation and migration; among others, topical administration of bLTF enhances wound closure (Takayama, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we confirmed for the first time that hLF induces a change in intracellular Ca 2+ levels in hADSCs and thereby increases hADSC-derived EV biogenesis. A recent study investigated the alteration of neutrophil calcium levels by using hLF in media containing Ca 2+ [29]. According to the authors, the addition of hLF to neutrophils resulted in transient calcium channel activation via tyrosine kinase and phospholipase C, and the activation of calcium channels by hLF was confirmed to be enhanced by the addition of CaCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hLF is used as a factor in human stem cell culture to increase the survival rate of stem cells via Fe 3+ ion transfer. Secondly, it has recently been confirmed that hLF is involved in the activation of Ca 2+ channels in human neurons and human neutrophils [28,29], which suggests that it may potentially enhance EV biogenesis from human stem cells. Finally, hLF is known to be effective in enhancing cell proliferation and ECM synthesis in target human cells [27,30,31].…”
Section: Introductionmentioning
confidence: 93%